Impaired innate immune gene profiling in airway smooth muscle cells from chronic cough patients. Issue 6 (15th November 2017) - Rossios, Christos; Pavlidis, Stelios; Gibeon, David; Mumby, Sharon; Durham, Andrew; Ojo, Oluwaseun; Horowitz, Daniel; Loza, Matt; Baribaud, Fred; Rao, Navin; Chung, Kian Fan; Adcock, Ian M.
Abstract : Chronic cough is associated with airway inflammation and remodelling. Abnormal airway smooth muscle cell (ASMC) function may underlie mechanisms of chronic cough. Our objective was to examine the transcriptome and focused secretome of ASMCs from chronic cough patients and healthy non-cough volunteers. ASMC gene expression profiling was performed at baseline and/or after stimulation with polyinosinic:polycytidylic acid (poly(I:C)) to mimic viral infection. Supernatants were collected for multiplex analysis. Our results showed no significant differentially expressed genes (DEGs, false discovery rate (FDR) <0.05) between chronic cough and healthy non-cough ASMCs at baseline. Poly(I:C) stimulation resulted in 212 DEGs (>1.5 fold-change, FDR <0.05) in ASMCs from chronic cough patients compared with 1674 DEGs in healthy non-cough volunteers. The top up-regulated genes included chemokine (C–X–C motif) ligand (CXCL) 11 ( CXCL11 ), CXCL10, chemokine (C–C motif) ligand (CCL) 5 ( CCL5 ) and interferon-induced protein 44 like ( IFI44L ) corresponding with inflammation and innate immune response pathways. ASMCs from cough subjects had enhanced activation of viral response pathways in response to poly(I:C) compared with healthy non-cough subjects, reduced activation of pathways involved in chronic inflammation and equivalent activation of neuroregulatory genes. The poly(I:C)-induced release of inflammatory mediators, including CXCL8, interleukin (IL)-6 and CXCL1, from ASMCs from cough patients was significantly impaired compared with healthy non-cough subjects. Addition of fluticasone propionate (FP) to poly(I:C)-treated ASMCs resulted in greater gene expression changes in healthy non-cough ASMCs. FP had a differential effect on poly(I:C)-induced mediator release between chronic cough and healthy non-cough volunteers. In conclusion, altered innate immune and inflammatory gene profiles within ASMCs, rather than infiltrating cells or nerves, may drive the cough response following respiratory viral infection.